Cause Analysis of Soft Caking of VAE Emulsion - Jixue Lv, Zhiwei Wang (Forest Chemicals Review, 1970)
VAE emulsion is one of the copolymerization compounds of vinyl acetate and ethylene, and it is a widely used environmental protection product. VAE emulsion is mainly used in adhesives, coatings, textiles/non-woven fabrics, building cement, paper and carpets, etc. In this paper, the causes of soft caking during storage of VAE emulsion were discussed by simulation experiment. The formation mechanism of soft caking was confirmed by reducing the solid content of emulsion and adjusting pH value. The distribution of emulsion particles and soft caking was observed by electron microscope (SEM), and then the composition and components of soft caking were further determined. The glass transition temperatures of emulsion and soft caking were compared by DSC, and it was confirmed by experiments that the water loss of emulsion surface layer was the main reason for the formation of soft caking, which could provide reference for the application and storage of VAE emulsion.